Financial sector development in the Pacific Rim - Itō, Takatoshi, 1950-; Rose, Andrew, 1959- (NBER-East Asia Seminar on Economics (Series) ;, 2009)
Examines the institutional factors influencing financial innovation, the consequences of financial development, widespread consolidation occurring through mergers and acquisitions, and the implementation of policy reform.--From publisher description.